Burkholderia pseudomallei Colony Morphotypes Show a Synchronized Metabolic Pattern after Acute Infection. - Philipp Gierok; Christian Kohler; Ivo Steinmetz; Michael Lalk (Public Library of Science (PLoS), 2016)
BACKGROUND:Burkholderia pseudomallei is a water and soil bacterium and the causative agent of melioidosis. A characteristic feature of this bacterium is the formation of different colony morphologies which can be isolated from environmental samples as well as from clinical samples, but can also be induced in vitro. Previous studies indicate that morphotypes can differ in a number of characteristics such as resistance to oxidative stress, cellular adhesion and intracellular replication. Yet the metabolic features of B. pseudomallei and its different morphotypes have not been examined in detail so far. Therefore, this study aimed to characterize the exometabolome of B. pseudomallei morphotypes and the impact of acute infection on their metabolic characteristics. METHODS AND PRINCIPAL FINDINGS:We applied nuclear magnetic resonance spectroscopy (1H-NMR) in a metabolic footprint approach to compare nutrition uptake and metabolite secretion of starvation induced morphotypes of the B. pseudomallei strains K96243 and E8. We observed gluconate production and uptake in all morphotype cultures. Our study also revealed that among all morphotypes amino acids could be classified with regard to their fast and slow consumption. In addition to these shared metabolic features, the morphotypes varied highly in amino acid uptake profiles, secretion of branched chain amino acid metabolites and carbon utilization. After intracellular passage in vitro or murine acute infection in vivo, we observed a switch of the various morphotypes towards a single morphotype and a synchronization of nutrient uptake and metabolite secretion. CONCLUSION:To our knowledge, this study provides first insights into the basic metabolism of B. pseudomallei and its colony morphotypes. Furthermore, our data suggest, that acute infection leads to the synchronization of B. pseudomallei colony morphology and metabolism through yet unknown host signals and bacterial mechanisms.